The effect of ICU diary on psychiatric symptoms after ICU discharge among adult critically ill patients: A prospective comparative study - Mami Shibata; Kyohei Miyamoto; Nozomu Shima; Tsuyoshi Nakashima; Junichi Fukushima; Shinichi Yamada; Sohei Kimoto; Shigeaki Inoue (Acute Medicine & Surgery)
Abstract Aim Psychiatric problems are common in critically ill patients after discharge from an intensive care unit (ICU). The effect of intensive care unit (ICU) diaries on psychiatric symptoms after ICU discharge was investigated in this prospective study. Methods Enrolled were critically ill adult patients who were emergently admitted to an ICU and expected to stay for at least 2 days. These patients received ICU diaries filled out by healthcare professionals and family members. Comparison was made with a historical cohort from a previous trial conducted in the same ICU but without ICU diaries. The primary outcome was the presence of significant post‐traumatic stress disorder (PTSD) symptoms 3 months after ICU discharge. Secondary outcomes included significant symptoms of anxiety and depression. Results Among 61 patients with ICU diaries, questionnaires were sent to 44 patients 3 months after ICU discharge; 29 patients responded and were analyzed (ICU diary group). Seventy‐four patients from a historical cohort were used as a control group. The proportion of patients with significant PTSD symptoms was 19% in the ICU diary group and 16% in the control group (adjusted odds ratio [aOR] [95% confidence interval: 95% CI]: 0.98 [0.26–3.70]). For anxiety and depression, the proportions were 25% and 29% in the ICU diary group, and 38% and 45% in the control group (aOR [95% CI]: 0.46 [0.15–1.38] for anxiety, aOR [95% CI] 0.40 [0.14–1.16] for depression). Conclusion ICU diaries were not associated with a reduced incidence of PTSD symptoms 3 months after ICU discharge.